Mathematical model of acyclic fuzzy control for traffic signal system with adaptive unconditional tram priority - Lytvynenko, M.; Rebezyuk, L. (ХНУРЕ, 2022)
The mathematical model of automatic control of the traffic signals system is proposed, which implements adaptive unconditional priority for the tram approaching the intersection. The mathematical model is based on a fuzzy control law and considers the dynamics characteristics of the tram from the moment it is registered by the intersection entry detector. An example of the proposed model application in the simulation for a complex intersection is provided and a comparative analysis of the obtained time characteristics of traffic flows for fuzzy control and existing adaptive methods that do not implement the tram signal priority is performed.
Keywords: acyclic fuzzy control; traffic signal system